How animals care for their babies - Hirschland, Roger B. (Washington, D.C. : National Geographic Society, 1987)
Depicts different kinds of parental behavior among a variety of animals, including the trumpeter swan, mountain goat, and baboon.
Bibliography: p. [34].
Keywords: Parental behavior in animals -- Juvenile literature; Animals -- Infancy -- Juvenile literature